Mississippi Social Studies Curriculum Framework, 1998 - Mississippi State Dept. of Education, Jackson; Mississippi State Dept. of Education, Jackson ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1998)
The primary purpose of this Mississippi social studies framework is to promote an understanding of the world, human interaction, cultural diversity, and cultural heritage and to equip students with the knowledge and understanding of the past, which is essential for coping with the present and planning for the future. The framework states that the social studies curriculum should provide teachers with a guide to help instruct students with the essential skills for problem solving and thoughtful decision making. Social studies should contain a specific body of knowledge that is divided into "strands" to focus on history, geography, civics, economics and other social sciences. Following an introduction that offers suggested objectives, curriculum guide, benchmarks, and divisions for elementary, middle grades, and upper grades, the framework is divided into the following sections: (1) "Kindergarten"; (2) "First Grade"; (3) "Second Grade"; (4) "Third Grade"; (5) "Fourth Grade" (Mississippi Studies); (6) "Fifth Grade" (United States Studies); (7) "Sixth Grade" (Western Hemisphere Studies); (8) "Seventh Grade" (Eastern Hemisphere Studies); (9) "Eighth Grade" (United States History to 1877); (10) "Mississippi Studies"; (11) "World History: 1750 to the Present"; (12) "United States History: 1877 to the Present"; (13) "United States Government"; (14) "Economics"; (15) "Introduction to World Geography"; (16) "Advanced World Geography"; (17) "Psychology"; (18) "Sociology"; (19) "Biblical History of the Ancient Middle East, 2000 B.C. to 100 A.D."; (20) "Local Resource Studies"; (21) "Law Related Education"; (22) "Problems in American Democracy"; (23) "Global Studies"; (24) "Minority Studies"; (25) "Humanities I"; (26) "Humanities II"; (27) "Introduction to the Social Studies"; (28) "Local Culture"; (29) "Future Studies"; (30) "Field Experiences"; (31) "Social Studies and Literature Connections"; (31) "Technology Connections"; and (32) "Assessment Glossary." (BT)
Availability: Mississippi Department of Education, P.O. Box 771, Jackson, MS 39205. Tel: 601-359-3778. For full text: http://www.mde.k12.ms.us.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Standards; Civics; Economics; Elementary Secondary Education; Geography; History; Learning Strategies; Public Schools; Social Studies; State Curriculum Guides; State Standards; Student Educational Objectives; United States Government (Course); Mississippi; Guides, Non-Classroom.